Enhancing undergraduate students’ academic writing skills through self-assessment - Cad, Ana Cecilia; Carrera, Paul Alexis (Letras, 2023)
Developing the knowledge and the skill to master academic writing in higher education constitutes a challenge for most undergraduate students. However, learning about this style of writing opens students’ doors to the wide world of academia. Thus, some undergraduate students were invited to become members of a Writing Feedback Center in which they worked with a tutor and a self-assessment sheet on different writing assignments following an eclectic approach to writing. In this work we analyzed students’ and tutors’ perceptions on self-assessment in relation to the development of their academic skill.